Two New Measures of Bankruptcy Efficiency - Ricardo Brogi; Paolo Santella (SUERF - The European Money and Finance Forum, 2004)
This study is aimed at developing new empirical models for evaluating the efficiency of bankruptcy legislations. The paper is divided in three parts. In the first part, we analyze from a conceptual point of view the effects on debtor firms of the lack of creditors' powers in bankruptcy. In the second part, we develop a new rating method for bankruptcy legislations according to their degree of creditors protection and apply it to five European countries. In the third part, we introduce a new approach for empirically estimating the efficiency of bankruptcy legislation based on the cost of banking credit and we test it on the Italian case. In particular, the unprecedented tool being used in the third section consists of the New Basel Capital Accord, i.e. the capital adequacy regulatory framework that is about to be put into effect as of the end of 2006.
Keywords: G33; 330; Bankruptcy; insolvency; corporate governance; banking; regulation efficiency; Insolvenz; Bewertung; Schätzung; Italien; Basler Akkord